The effects of ACE-I and ARB on peritoneal albumin loss and serum albumin levels in peritoneal dialysis patients - (:unkn) unknown (My University, 2003)
Objective: Anti-proteinuric effects of angiotensin converting enzyme inhibitors (ACE-I) and angiotensin receptor blockers (ARB) have been established in various renal diseases. However, the effects of ACE-I and ARB on the permeability of peritoneal membrane are unknown and the effect of ACE-I and ARB use on peritoneal permeability in patients undergoing continuous ambulatory peritoneal dialysis has not been studied. Methods: Fifty non-diabetic patients with high peritoneal permeability, who had been on a regular peritoneal dialysis (PD) treatment for at least one year, were included in the study. The patients were prospectively randomized either fosinopril 10 mg/day p.o (n=25) (group 1) or valsartan 80 mg/day p.o (n=25) (group 2) for 12 months. All patients received standard 35-cal/kg/day diets with 1.2-g/kg/day protein intake and strict salt restriction. All patients were on standard PD program (2 L; 1.36%, 4 exchanges/day). Annual mean serum albumin level, calculated from the monthly serum albumin level and peritoneal albumin values obtained from the dialysate after 8 hours, dwell on two occasions 6 months apart were measured twice yearly. Results: A significant increase in the serum albumin values, (3.68±0.56 g/dl vs. 3.94±0.46 g/dl, p<0.0001) a significant decrease in peritoneal fluid albumin values (9.06±2.65 g/dl vs. 7.08±1.43 g/dl, p<0.01) were observed in the ACE-I group following the treatment. While no significant change (3.75±0.48 g/dl vs. 3.87±0.37 g/dl, p>0.05) was observed in the serum albumin values, a significant decrease (8.62±3.87 g/dl vs. 5.84±2.94 g/dl, p<0.01) was obtained in peritoneal fluid albumin values for the ARB group. Conclusion: At the end of the study a significant decrease was observed in the peritoneal protein values for patients on ACE-I and ARB.
Keywords: Angiotensin converting enzyme inhibitor; Angiotensin receptor blocker and albumin; Peritoneal dialysis